Contents (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2016)
25 cm

Sprawozdania Archeologiczne T. 61 (2009), Spis treści (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2009)
S. 5-7 ; 25 cm
Keywords: archeologia

Sprawozdania Archeologiczne T. 61 (2009), Recenzje - Florkiewicz, Iwona (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2009)
S. 515-534 ; 25 cm
Bibliogr s. 523-525
Tekst równolegle w jęz. niem. i pol.
Aleksandr V. Simonenko, Ivan I. Marčenko, Natal’ja Ju. Limberis, Römische Importe in sarmatischen und maiotischen Gräbern zwischen Unterer Donau und Kuban (= Archäologie in Eurasien 25), mit der Einleitung von Hermann Parzinger, Mainz 2008
Keywords: archeologia

Sprawozdania Archeologiczne T. 61 (2009), Recenzje - Buchner, Aneta (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2009)
S. 503-514 ; 25 cm
Bibliogr s. 509
Tekst równolegle w jęz. niem. i pol.
Marcin S. Przybyła, Wojciech Blajer, Struktury osadnicze w epoce brązu i wczesnej epoce żelaza na obszarze podkarpackiej wysoczyzny lessowej między Wisłokiem i Sanem [Besiedlungsstrukturen in der Bronze- und Früheisenzeit auf dem Gebiet der vorkarpatischen - Lößhochebene zwischen den Flüssen Wisłok und San], Wydawnictwo Uniwersytetu Jagiellońskiego, Kraków 2008
Keywords: archeologia

Sprawozdania Archeologiczne T. 61 (2009), Recenzje - Włodarczak, Piotr (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2009)
S. 473-502 ; 25 cm
Bibliogr. s. 488
Tekst równolegle w jęz. niem. i pol.
Walter Dörfler, Johannes Müller (Hrsg.), Umwelt - Wirtschaft - Siedlungen im dritten vorchristlichen Jahrtausend Mitteleuropas und Südskandinaviens. Internationale Tagung Kiel 4.-6. November 2005 (= Offa Bücher 84). Neumünster, 2008
Keywords: archeologia

Sprawozdania Archeologiczne T. 61 (2009), Recenzje - Pawleta, Michał (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2009)
S. 451-463 ; 25 cm
Bibliogr. s. 456-457
Tekst równolegle w jęz. ang. i pol.
Aleksander Dzbyński. 2008. Rytuał i porozumienie. Racjonalne podstawy komunikacji i wymiany w pradziejach Europy Środkowej/ Ritual and understanding. Rational bases of communication and exchange in prehistoric Central Europe (= Collectio Archaeologica Ressoviensis 8). Instytut Archeologii Uniwersytetu Rzeszowskiego. Rzeszów; 291 pages, 111 figures, 10 tables. Bilingual (Polish and English) publication.
Keywords: archeologia

Sprawozdania Archeologiczne T. 61 (2009), Recenzje - Witkowska, Barbara (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2009)
S. 465-472 ; 25 cm
Bibliogr. s. 468
Tekst równolegle w jęz. ang. i pol.
Renata Zych, Kultura pucharów lejkowatych w Polsce południowo-wschodniej. The Funnel Beaker Culture in Southeastern Poland (= Collectio Archaeologica Ressoviensis 7), Rzeszów 2008
Keywords: archeologia

Sprawozdania Archeologiczne T. 61 (2009), Recenzje - Kołodziej, Barbara (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2009)
S. 437-450 ; 25 cm
Bibliogr. s. 443
Tekst równolegle w jęz. ang. i pol.
Ian Hodder, Çatalhöyük. The leopard’s tale, London 2006
Keywords: archeologia

Baltic Amber in Hungarian Bronze Age. New data and current stage of research - Jaeger, Mateusz; Kulcsár, Gabriella; Melis, Eszter; Stróżyk, Mateusz; Piszora, Paweł; Csányi, Marietta; Csuvár-Andrási, Réka; Fischl, Klára P.; Guba, Szilvia; Pap, Evelin; Pásztor, Emília; Patay, Róbert; et al. (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
Amber was one of the key raw materials distributed in Bronze Age Europe. One of its varieties – succinite – was exchanged over a vast area stretching from its sources on the southern shores of the Baltic Sea to the shores of the Mediterranean Sea. The chemical identification of Baltic amber significantly expands our knowledge of the dynamics and nature of the relationships connecting different regions of Europe in the first half of the second millennium BC. One of the most significant cultural-geographical areas reached by this amber was the Carpathian Basin. This text presents a summary of the current state of knowledge about the context, chronology, and the extent of amber occurrence in the Hungarian Bronze Age. At the same time, it supplements the catalogue of finds with artefacts acquired in recent years, providing new information regarding radiocarbon dating and spectral analysis of selected amber artifacts.
il. ; 25 cm
Keywords: archeologia; Baltic amber; Carpathian Basin; Hungarian Bronze Age; prehistoric exchange; spectral analysis; absolute chronology

Tracing the micro processes of the production and use of ceramic vessels and textile products from the Cucuteni-Trypillia settlements of Bilyi Kamin and Krynychky-Ferma (Ukraine)) - Rud, Vitalii; Zaitseva, Olha; Skrzyniecka, Weronika; Kosakivskyi, Viktor; Hofmann, Robert (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
The article presents an analysis of a collection of ceramic fragments with textile imprints from the Cucuteni-Trypillia settlements of Bilyi Kamin and Krynychky-Ferma, which are situated in modern Ukraine. The analysis involved macroscopic and microscopic examinations as well as use-wear studies, aimed at characterizing traces that provide insights into the production and utilization of ceramic vessels and textile products. A comparison of results with published data from the Trypillia settlements located mainly to the east of the Dnister River was carried out. A preliminary characterization of the shared and distinct characteristics in the development of the economic activities during the Trypillia CI and CII stages (i.e., during 4th millennium BC), was completed.
il. ; 25 cm
Keywords: archeologia; Cucuteni-Trypillia; ceramics; textile impressions; microscopic analysis; use-wear; ceramic and textile production

Early Bronze Age Pamukli bair barrow near Malomirovo and the problem of east-oriented barrow graves in Upper Thrace - Alexandrov, Stefan; Włodarczak, Piotr (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
In 2021, excavations of a barrow were conducted on the Pamukli Bair hill in Malomirovo, Elhovo municipality, Upper Thrace, Bulgaria. These excavations yielded a remarkable discovery – a sequence of graves dating back to the late fourth and third millennium BC. Notably, these findings prominently featured elements of the early Pit-Grave culture, also known as the Yamna culture. However, the commencement of this burial sequence was marked by graves that diverged from the norms of the Yamna culture. These early graves contained individuals interred in a crouched position, with their heads oriented towards the east. Unlike the prevalent use of ochre in the Yamna culture, this type of funeral ritual exhibited a limited presence of ochre. Comparable central graves of this kind have also been documented in other barrows throughout the Middle Tundzha region and various parts of Upper Thrace, particularly in the “Maritsa-Iztok” area. These burials can be dated to the end of the fourth millennium BC and display similarities to both local funeral traditions (Ezero A1) and graves analogous to the Cernavodă/Nizhna Mikhailivka traditions. The horizon of barrow necropolises featuring these distinctive burials is clearly discernible within the Upper Thrace region and seamlessly connects to the horizon of the early Pit-Grave culture.
il. ; 25 cm
Keywords: archeologia; barrows; Early Bronze Age; Upper Thrace; absolute chronology; funeral rite

Was Gordineşti II-Stînca Goala abandoned due to cultural changes or environmental impacts? A case of the late Trypillia settlement in northern Moldova - Rybicka, Małgorzata; Wacnik, Agnieszka; Pokutta, Dalia; Kittel, Piotr; Okupny, Daniel; Król, Dariusz; Sady-Bugajska, Agata; Pankowski, Walenty; Sîrbu, Ghenadie; Makohonienko, Mirosław; Słowiński, Michał (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
This study aims to provide information on cultural and environmental factors influencing the development and decline of the Late Trypillia settlement at Gordineşti II–Stînca goală. The discussion is based on the results of archaeological excavations, non-invasive surveys (magnetometric and GPR), as well as radiocarbon, macroremains, palynological, archaeozoological, and isotopic analyses. All data suggests that Gordineşti II–Stînca goală consisted of at least 15 lightweight constructed dwellings. It was a small settlement existing c. 3300-2950 BC. Its inhabitants were oriented to cereal cultivation and livestock husbandry, using available areas with fertile soils. The livestock were well-fed. However, the location of the settlement on a highly exposed outcrop probably did not facilitate the use of the flowing water of the nearby Racovăţ River. The rock underlying the site would have made digging the wells a very tough task. Hence, the water access problem may be one of the factors that made life inconvenient at the Gordineşti II-Stînca goală settlement.
il. ; 25 cm
Keywords: archeologia; radiocarbon chronology; Palynology; stable isotopes; animal management; Late Trypilia; Gordineşti Group

Preface - Makarowicz, Przemysław; Szmyt, Marzena; Włodarczak, Piotr (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
il. ; 25 cm
Keywords: archeologia

Contents (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
25 cm
Keywords: archeologia

Early metallurgy of Ukraine of the Late 5th-4th Millennia BC: an outline - Ivanov, Mykyta (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
According to the classical model of the metallurgical raw material supply chain proposed by Eugeniy Chernykh, the Eneolithic and Early Bronze age cultures of Ukraine were completely dependent on imported raw material. It seems that the main supplier of metal, as well as some complete goods during the 5th and 4th Millennia BC, was the ‘Carpatho-Balkan Metallurgical Province (CBMP)’ while during the 3rd Millennium BC, the provision chain was reoriented towards the ‘Circumpontic Metallurgical Province (CMP)’. Yet, new discoveries that were made during the 1990s-2020s indicate the need for the amendment of such a model. This is the aim of the current paper. In the following text, the concept of four Ukrainian local metallurgical provinces and two metalworking foci will be introduced. The typology and dating of the recently discovered metal objects as well as metallurgical tools will be provided. The question of the existence of domestic metallurgical raw material deposits will be discussed.
il. ; 25 cm
Keywords: archeologia; Metallurgy; Eneolithic; Early Bronze Age; Trypillia; Ukraine

Trypillia culture pottery imports with attributes of the latest phase of the Trypillia CII stage in the Funnel Beaker culture settlement Zymne, western Ukraine - Havinskyi, Andrii; Rybicka, Małgorzata (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
When considering Trypillia Culture imports in the pottery assemblage of the Funnel Beaker Culture settlement in Zymne, many scholars have emphasized the significance of this evidence when conceptualizing connections between communities of both Cultures, and also highlight the chronological aspects of the matter. The available data make it possible to associate pottery assemblage from Zymne with Gordineşti group of the Trypillia CII stage which dates back to the time range from 3300 until 3000/2950 BC and corresponds to occupation phase II of the Funnel Beaker Culture in Gródek.
il. ; 25 cm
Keywords: archeologia; stage CII Trypilia Culture; FunelBeaker Culture; western Ukraine; Gordineşti group

Intrusions of the steppe population into the Balkan-Carpathian region in the Early Bronze Age: factors and aspects - Ivanova, Svitlana (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
The Budzhak culture of the Northwest Pontic region is a part of the Yamna cultural-historical area. Its social hierarchy and the identification of “ritual groups” within it provide important evidence when considering intrusions of the steppe population into the Balkan-Carpathian region. Certain elite grave goods are often associated with individuals buried in certain positions that allow the identification of “ritual groups”. One of these is characterized by supine inhumation with flexed legs, arms stretched along the body. These had high social status in the context of the Budzhak culture and they are the ones that were widespread in Europe. In addition to the well-known Danubian route, other paths from the steppe to the west can be considered (Carpathian-Transylvanian and Prut-Dnistr routes). The principal aim of the movement to the west was probably to obtain metals, which could be exchanged for salt from the estuaries of the Northwest Pontic area.
il. ; 25 cm
Keywords: archeologia; Budzhak culture; Yamna culture; social structure; exhange; metals; salt

Burials with the ochre of Corded Ware culture in the Upper Dnister region - Voitovych, Mariia (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
Burials with the ochre of the CWC on the territory of the Upper Dnister region, the higher concentration of which was recorded on the territory of the right bank of the Dnister river, within the Drohobych Upland, were considered. It has been established that now about 30 burials were found on this territory, in which this mineral substance was found, evidenced both inside the burials and at the level of the ancient horizon under the barrow mounds. It was observed that the body of the deceased was covered with ochre, or it was placed as separate lumps inside the burial. It is noted that the remains of wooden structures in the form of flooring and ceilings are often present in burials with ochre. It was defined that burials with the ochre of the CWC on the territory of Upper Dnister region date to the period of the first half of the 3rd millennium B. C. and are related to influences from the environment of Yamna culture.
il. ; 25 cm
Keywords: archeologia; Corded Ware culture; Yamna culture; ochre; burial; wooden construction

Following the traces of the earliest Corded Ware in Moravia and steppe elements in its content - Peška, Jaroslav (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
The earliest Corded Ware is very poorly represented in Moravia (several type A, Moravian-type, hammer-axes, settlements with the so-called Wellenleistentöpfe: Olomouc-Slavonín, Horní lán) and the situation is not much better even in the earlier Moravian Corded Ware Culture (MCWC) period (the Palonín settlement, graves at: Dub nad Moravou, Hradisko u Kroměříže, Němetice). Among the local MCWC (over 90%; 2700/2600 2400/2200 calBC) we find a number of components linking this to Eastern Europe both in the burial ritual (grooves around graves, internal construction, burials in the frog position, graves of metallurgists) and in the material content (daggers/razors with a tang, hammer-shaped pins, a beaker decorated with a cord and a fishbone motif) with numerous analogues in the Yamna and Catacombna cultures of the Carpathian, Balkan and northern Pontus. Most surprising is a group of MCWC graves with grooves at the bottom, interpreted as burials on all-wood four-wheeled ceremonial wagons with direct counterparts in the Maikop, Yamna, and Catacombna cultures of eastern Europe.
il. ; 25 cm
Keywords: archeologia; Moravia; Moravian Corded Ware Culture; Eastern European elements; Yamna culture; Catacomb culture; wagon burials

New radiocarbon dates for the Criş site of Sacarovca I (Moldova) - Kiosak, Dmytro; Dergaciov, Valentin A.; Szidat, Soenke; Tinner, Willy (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
Four new AMS radiocarbon dates shed new light on the chronology of one of the easternmost sites of the Criş culture. The conventional dating efforts had yielded indecisive results, while the new results correspond well to the typo-chronological position of the site (Criş IV) and the chronology of other sites with similar finds. The comparison with the nearby para-Neolithic sites demonstrated that the establishment of the para Neolithic way of life (foragers equipped with pottery) in the region happened several centuries before the spread of early farmers of the Criş culture into Moldova.
il. ; 25 cm
Keywords: archeologia; Early Neolithic; radiocarbon dating; Bayesian modeling; early farming colonization; indigenous foragers

Rediscovering a Middle Bronze Age cemetery – the barrow necropolis in Pidhoroddya, Western Ukraine - Romaniszyn, Jan; Niebieszczański, Jakub; Cwaliński, Mateusz; Rud, Vitalii; Kochkin, Ihor; Makarowicz, Przemysław (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
The following article presents the archaeological revaluation of the Middle Bronze Age Komarów culture cemetery of Pidhoroddya in Western Ukraine in the Pre-Carpathian region. By examining scarce archival information from the pre-Second World War period, the Polish-Ukrainian research team brought to light evidence of a vast cemetery complex in Pidhoroddya, consisting of 39 barrows. The applied combination of archaeological survey, drilling, and magnetometry prospection revealed aspects of the spatial arrangement of the Komarów culture necropolis, as well as details of the funeral architecture, which allowed associating the burial mounds with the known canon of Komarów culture rites. This study presents the results of the archival research, followed by non-invasive survey, and their potential for revaluating the present state of knowledge regarding this barrow cemetery.
il. ; 25 cm
Keywords: archeologia; Pidhoroddya Barrow Cemetery; Middle Bronze Age; geophysical survey; landscape archaeology; Funerary architecture; Komarów culture

Yampil barrows from the fourth and IIIrd millenium BC in the light of Polish-Ukrainian investigations 2010-2014 - Kośko, Aleksander; Klochko, Viktor I.; Potupchyk, Mikhailo; Włodarczak, Piotr; Żurkiewicz, Danuta (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
In the vicinity of Yampil (Vinnytsia oblast, Ukraine), there exists a cluster of barrows dating back to the Eneolithic and Early Bronze Age. Nestled upon the Podillia Upland, this concentration lies at the crossroads of two cultural spheres: the Eastern European steppe and Central European. The exploration of the Yampil barrows began during the 1980s by archaeologists from Vinnytsia. This endeavor was enriched by a Polish-Ukrainian expedition that conducted fieldwork from 2010 to 2014. Seven barrows were then examined. Today, an abundance of radiocarbon data empowers us to construct a precise chronological framework for the Yampil barrow graves. We can now discern four principal stages in this sequence: (1) late Eneolithic, (2) early Yamna, (3) late Yamna era, and (4) Catacombna. During the first two periods (3350-2800 calBC), these barrows were meticulously constructed, sometimes evolving in multiple phases. In the latter two stages (2800-2400 calBC), cemeteries took shape, marked by graves thoughtfully dug into the fully formed mounds.
il. ; 25 cm
Keywords: archeologia; late Eneolithic; Early Bronze Age; Podillia; barrows; Yamna culture; Yampil

Barrows in the forest-steppe between the Dniester and Southern Bug, Ukraine. Initial results of comprehensive research - Szmyt, Marzena; Włodarczak, Piotr; Hildebrandt-Radke, Iwona; Potupchyk, Mykhailo; Przybyła, Marcin M.; Rud, Vitalii; Shelekhan, Oleksandr; Szczepanek, Anita; Żurkiewicz, Danuta; Ławniczak, Marcin; Podsiadło, Michał (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
The article presents the preliminary results of research by a Polish-Ukrainian team who in 2018-2023 worked on the project of comprehensive exploration of barrows situated in the forest-steppe between the Southern Bug and Dniester in modern Ukraine. There, two major stages of erecting and using barrows were distinguished for the 3rd and 1st millennia BC. Two barrows discussed herein, explored as part of the project, were erected in the second stage. Barrow 3 in Ivanivtsi-Antonivka can be dated to the second half of the 10th – first half of the 8th century BC, whereas Barrow 6 in Sloboda Noskovetska to the late 8th – early 7th century BC. The older one was erected and then used by communities related to the early period of the Chornolis culture. The younger one is at present one of the main pre-Scythian complexes of eastern Podillia. The multi-component set of artefacts deposited under its mound represents a mixture of the Chornolis culture, Basarabi-Şoldăneşti influences and impact of early steppe nomads (Cimmerians?). It illustrates well a complex cultural mosaic found in the forest-steppe between the Southern Bug and Dniester rivers.
il. ; 25 cm
Keywords: archeologia; barrows; Eastern Podillia; 1st millennium BC; Chornolis culture; Basarabi-Şoldăneşti culture; early nomads impact

Funeral rite in the mound of Scythian time near Vasyne - Kozyr, Iryna; Panchenko, Kyrylo; Chornyi, Oleksandr (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
The article is devoted to an analysis of the funeral rite from the mound near the village of Vasyne in Kirovohrad region. The site is located on the border of the Dnipro right-bank forest-steppe and steppe. The main Scythian burial was deposited in a wooden chamber on the ancient ground surface. A complex wooden burial structure of oak timbers constructed over it was partially burnt, but was well preserved. The remains of artefacts found in the burial site, including fragments of ancient amphoras, among them plump-throated Chios, thin-walled antique black-figured kylix, fragments of ceramic vessels, and animal bones. Undoubtedly, the most interesting find was a stone anthropomorphic stele of grey granite. The complex dates to the first quarter of the 5th century BC.
il. ; 25 cm
Keywords: archeologia; barrow; Scythian time; mound; anthropomorphic stele; trizna ritual

Second life of damaged things: repairing and modifying jewellery from the Crimea in the Sarmatian period - Polit, Beata (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2023)
Crimean jewellery from the Sarmatian period (2nd century BC – 4th century AD) includes a small but interesting group of adornments with traces of damage and repair. These artefacts were elements of grave inventories of the people of the Late Scythian and Sarmatian cultures – deposited exclusively in female and child graves. Most of the repaired personal ornaments are earrings and bracelets. Their quality is usually very low. The existence of repairs made jewellery look less attractive and they were limited to modifications allowing their owners to use such adornments again. The general quality of the repairs seems to indicate that they were performed by people lacking expert knowledge of jewellery making.
il. ; 25 cm
Keywords: archeologia; Ukraine; Crimean Peninsula; Sarmatian period; jewellery; repairs